Almost sure functional central limit theorems for multiparameter stochastic processes - Czerebak-Morozowicz, E.B.; Rychlik, Z.; Urbanek, M. (Condensed Matter Physics, 2008)
We present almost sure central limit theorems for stochastic processes whose time parameter ranges over
the d-dimensional unit cube. Our purpose here is to generalize the classic functional central limit theorem of
Prokhorov (1956) for such processes. We prove multidimensional analogues of Glivenko-Cantelli type theorems. Ми подаємо майже певнi центральнi граничнi теореми для стохастичних процесiв з часовим параметром, що змiнюється у α-вимiрному одиничному кубi. Нашою метою є узагальнення класичної функцiональної центральної граничної теореми Прохорова (1956) для таких процесiв. Ми доводимо багатовимiрнi аналоги теореми типу Глiвенко-Кантелi.